Садан төрлийн хамаат хэллэгт илрэх япон монгол хүний сэтгэлгээний онцлог: Features of phrases related to relatedness in the Japanese and Mongolian mentalities - Ц., Онон (Mongolian Studies, 2023)
The soul of the word is its meaning that reveals the development of the real world through the language which is used for. A word has a definite meaning, in fact, but can be determined by more different meanings based on many factories like language development, process of word usage and social cultural changes. One of these features is focused on idioms. We attempted to analyze the national mentality from some proper nouns and idioms which are formed by a word, used “Relative” through this article. According to the idioms, it represents not only the negative evaluation in Mongolian language. But in Japanese, it represents negative evaluations.